Refugees on the Move Crisis and Response in Turkey and Europe (Volume 45) - Balkan, Erol; Kutlu-Tonak, Zümray (Berghahn Books, 2022)
Refugees on the Move highlights and explores the profound complexities of the current refugee issue by focusing specifically on Syrian refugees in Turkey and other European countries and responses from the host countries involved. It examines the causes of the movement of refugee populations, the difficulties they face during their journeys, the daily challenges and obstacles they experience, and host governments' attempts to manage and overcome the so-called "refugee crisis."